2009
DOI: 10.1088/0957-4484/20/16/165303
|View full text |Cite
|
Sign up to set email alerts
|

One-step inkjet printing of conductive silver tracks on polymer substrates

Abstract: A one-step process to fabricate conductive features on flexible polymer substrates by inkjet printing an organometallic silver ink directly onto a substrate that is heated to 130 degrees C is presented. This process led to the immediate sintering of the printed features. The samples were left for 5 min at elevated temperature, which resulted in conductive silver features with a resistivity of eight times the bulk silver value. The combination of this ink and the simultaneous printing/sintering process opens up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
134
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 213 publications
(141 citation statements)
references
References 35 publications
5
134
0
2
Order By: Relevance
“…Recently Perelaer et al developed a one-step inkjet process to produce metal lines on glass and on plastic foils [204]. Silver salt ink with viscosity of 10 cP was jetted directly onto the pre-heated substrate triggering solvent evaporation and sintering as a combined process.…”
Section: Silver Inksmentioning
confidence: 99%
“…Recently Perelaer et al developed a one-step inkjet process to produce metal lines on glass and on plastic foils [204]. Silver salt ink with viscosity of 10 cP was jetted directly onto the pre-heated substrate triggering solvent evaporation and sintering as a combined process.…”
Section: Silver Inksmentioning
confidence: 99%
“…Wettability plays a key role in various industrial applications (e.g., material dispersion and interfacial chemistry). In particular, it significantly affects the coating industry, which includes nano engineering, ink, paint, paste, and adhesives; as well as the compound industry, which includes extrusion, injection molding, and casting [8][9][10][11][12][13]. Surface energy is the energy created by surface atoms, and is the result of the force of attraction they exert on external materials.…”
mentioning
confidence: 99%
“…These MOD inks have been used for inkjet printing since the late 1980s (Vest et al, 1983). In order to obtain metal features, a conversion of organometallic silver inks is required, which usually takes place at relatively low temperatures below 200 °C (Wu et al, 2007), although temperatures below 150 °C have been reported as well (Smith et al, 2006, Perelaer et al, 2009a. The typical metal loading of organometallic inks is 10 to 20 wt%.…”
Section: Methods For Sintering Nanoparticle Inksmentioning
confidence: 99%